2017
DOI: 10.1016/j.jpsychires.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Childhood trauma, dimensions of psychopathology and the clinical expression of bipolar disorders: A pathway analysis

Abstract: This study provides refinement of the links between early adversity, dimensions of psychopathology and the complexity/severity of BD. Mainly, dimensions of affective dysregulation, impulsivity/hostility partially mediate the links between childhood emotional to suicide attempts and substance misuse in BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 72 publications
(86 reference statements)
4
22
0
7
Order By: Relevance
“…[71][72][73] Among all subtypes of CM, we found that emotional abuse; sexual abuse and emotional neglect might have a greater contribution to SB in BD. These findings are in line with studies by Etain et al, 38,74 which show that emotional abuse is closely related to worse clinical outcomes in BD, including SB. In addition, sexual abuse seems to be a strong predictor for suicide.…”
Section: Discussionsupporting
confidence: 92%
“…[71][72][73] Among all subtypes of CM, we found that emotional abuse; sexual abuse and emotional neglect might have a greater contribution to SB in BD. These findings are in line with studies by Etain et al, 38,74 which show that emotional abuse is closely related to worse clinical outcomes in BD, including SB. In addition, sexual abuse seems to be a strong predictor for suicide.…”
Section: Discussionsupporting
confidence: 92%
“…Impulsivity may mediate the relationship between childhood maltreatment and increased risk for developing alcohol/cannabis abuse [172]. Etain et al (2017) conducted a path-analysis in 485 euthymic bipolar disorder patients and uncovered a significant association between impulsivity and emotional abuse, and impulsivity was associated with increased risk for SUDs [173]. These studies suggest that in some individuals with a history of childhood maltreatment, albeit not all, interventions that focus on alcohol/drug use problems, and specifically externalizing behaviors that may mediate the link between childhood maltreatment and alcohol/drug use problems (e.g.…”
Section: Pathways To Mood Disorder Outcomes-more Work On Mechanisms Amentioning
confidence: 99%
“…Moreover, there are consistent findings across studies in BD that childhood maltreatment is associated with a more severe and complex clinical expression of the disorder. Indeed, when exposed to childhood maltreatment, patients with BD will present with an earlier age of onset, more major mood episodes, and an increased risk for suicide attempts and rapid cycling course . In the meta‐analysis published by Agnew‐Blais in 2016, childhood maltreatment is associated with all the 12 indicators of severe or complex course of BD, including greater number of manic and depressive episodes, greater mania, depression and psychosis severity, higher risk of comorbidity with post‐traumatic stress disorder, anxiety disorders and substance use disorders, earlier age at onset, higher risk of rapid cycling and suicide attempt …”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when exposed to childhood maltreatment, patients with BD will present with an earlier age of onset, more major mood episodes, and an increased risk for suicide attempts and rapid cycling course. [4][5][6][7] In the meta-analysis published by Agnew-Blais in 2016, childhood maltreatment is associated with all the 12 indicators of severe or complex course of BD, including greater number of manic and depressive episodes, greater mania, depression and psychosis severity, higher risk of comorbidity with post-traumatic stress disorder, anxiety disorders and substance use disorders, earlier age at onset, higher risk of rapid cycling and suicide attempt. 8 Gene-environment interactions have been suggested to be at stake when investigating the severity and/or complexity of the clinical expression of BD.…”
Section: Introductionmentioning
confidence: 99%